2022
DOI: 10.3390/s22134982
|View full text |Cite
|
Sign up to set email alerts
|

PD Flexible Built-In High-Sensitivity Elliptical Monopole Antenna Sensor

Abstract: In view of the insufficient signal detection sensitivity of Gas Insulated Switchgear (GIS), partial discharge (PD), ultra-high frequency (UHF), and failure to conform with GIS surface structure when the existing rigid stereo structure UHF sensor is built in, this paper, using rectangular patch antenna equivalent technique, trapezoidal ground plane technique, and coplanar waveguide (CPW) feed line index asymptotic linearization technique, conducts research on a flexible built-in high-sensitivity elliptic monopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In band of 1-3 GHz, the proposed UHF sensor has higher detection sensitivity in the frequency band of 1-3 GHz, and lower detection sensitivity in the frequency band of 0.3-1 GHz. 2 The proposed UHF sensor sensitivity test experiment is carried out on 220 kV GIS experiment circuit according to IEC 60270 and GB/T 7354-2018. The experimental results show that the UHF sensor proposed in this paper can stably detect the PD electromagnetic wave signal leaking from the resin hole, and signal frequency spectrum characteristics is consistent with the sensor detection band, and the theoretical analysis of EM wave propagation characteristics from rectangular resin hole.…”
Section: Experimental Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In band of 1-3 GHz, the proposed UHF sensor has higher detection sensitivity in the frequency band of 1-3 GHz, and lower detection sensitivity in the frequency band of 0.3-1 GHz. 2 The proposed UHF sensor sensitivity test experiment is carried out on 220 kV GIS experiment circuit according to IEC 60270 and GB/T 7354-2018. The experimental results show that the UHF sensor proposed in this paper can stably detect the PD electromagnetic wave signal leaking from the resin hole, and signal frequency spectrum characteristics is consistent with the sensor detection band, and the theoretical analysis of EM wave propagation characteristics from rectangular resin hole.…”
Section: Experimental Results Analysismentioning
confidence: 99%
“…Therefore, it is necessary to conduct effectively on-line monitoring of the slowly developing PD (Partial Discharge) insulation defect, obtain the defect severity in advance, and repair it before the defect reaches a certain severity. At present, the methods used for on-line monitoring of GIS PD insulation defect mainly include UHF method, ultrasonic method and optical detection method, etc., [1][2][3][4]. Due to its high reliability and high sensitivity, etc., the UHF method has been widely studied and applied in the field of GIS PD insulation monitoring [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For the creation of flexible, built-in GIS PD detection UHF antenna sensors, our group has developed a variety of UHF GIS PD detection antennas based on two PD flexible UHF antenna sensor substrates, namely thermosetting polyimide (PI) and polydimethylsiloxane (SU-8/PDMS). These flexible antennas have obvious advantages such as ultra-small sizes (maximum sizes of less than 60 mm), ultra-thinness (thicknesses of up to 0.2 mm), excellent radiation performances and stable performances in the bending radius deformation range of 150-500 mm [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Partial discharge defects are one of the main causes of GIS failure, which causes SF 6 gas to decompose at high temperatures and generate symbolic decomposition products such as SO 2 . Previous studies have shown that the identification and evaluation of partial discharge defects can be achieved by analyzing information such as the type, concentration, and growth trend of the SF 6 decomposition components [3][4][5].…”
Section: Introductionmentioning
confidence: 99%